Intermittent Flow Regimes in a Transonic Fan Airfoil Cascade - J. Lepicovsky; E. R. McFarland; R. V. Chima; V. R. Capece; J. Hayden (International Journal of Rotating Machinery)
A study was conducted in the NASA Glenn Research Center (NASA-GRC) linear cascade on the intermittent flow on the suction surface of an airfoil section from the tip region of a modern low aspect ratio fan blade. Experimental results revealed that, at a large incidence angle, a range of transonic inlet Mach numbers exist where the leading-edge shock-wave pattern was unstable. Flush-mounted, high-frequency response pressure transducers indicated large local jumps in the pressure in the leading edge area, which generates large intermittent loading on the blade leading edge. These measurements suggest that for an inlet Mach number between 0.9 and 1.0, the flow is bi-stable, randomly switching between subsonic and supersonic flows. Hence, it appears that the change in overall flow conditions in the transonic region is based on the rate of switching between two stable flow states rather than on the continuous increase of the flow velocity.To date, this flow behavior has only been observed in a linear transonic cascade. Further research is necessary to confirm this phenomenon occurs in actual transonic fans and is not the by-product of an endwall restricted linear cascade.